Observing the Working Alliance in Videoconferencing Psychotherapy for Alcohol Addiction: Reliability and Validity of the Working Alliance Inventory Short Revised Observer - Ribeiro, Nathálya Soares; Colugnati, Fernando Antonio Basile; Kazantzis, Nikolaos; Sartes, Laisa Marcorela Andreoli (Frontiers in Psychology, 2021)
The COVID-19 pandemic has affected mental health and alcohol consumption among individuals. Videoconferencing psychotherapy has become a fundamental treatment for people with alcohol use disorders. However, there are still doubts about its effectiveness and the therapeutic relationship. The working alliance is considered a foundation of effective practice in Cognitive Behavior Therapy (CBT). Observer measurements of the working alliance have demonstrated reliability and meaningful associations with reduction of symptoms. However, translations of instruments to evaluate the working alliance and examine its construct have not previously been conducted for online psychotherapy for alcohol addiction. The present study aimed at the cross-cultural adaptation of the Working Alliance Inventory-Short Form-Observer (WAI-SR-O) for Brazil and the evaluation of its reliability and evidence of its validity in videoconferencing psychotherapy for alcoholism. The WAI-SR-O was applied by pairs of observers for the evaluation of the working alliance in 19 recorded sessions of videoconferencing psychotherapy of 10 clients with a diagnosis of alcohol addiction. The sessions were also evaluated by the therapist (WAI-T) and client (WAI-C). The WAI-SR-O shows moderate inter-rater ICC (ICC = 0.67) for the general scale, higher ICC for the goals and bond subscales, but a moderate value for the task subscale. The internal consistency was good (a = 0.86). Results show low but significant correlations among the goals and bond subscales of the WAI-SR-O and the general, goals and bond scales of the WAI-T. No correlations were found with the WAI-C. As the literature points out, the client, therapist, and observer versions of the WAI evaluated the alliance differently, requiring further study. The WAI-SR-O proved to be a reliable and valid measurement for evaluation of the working alliance in videoconferencing psychotherapy for alcohol addiction, becoming an important tool for the study of the working alliance in telepsychotherapy.